Long‐Chain Alkylimidazolium Ionic Liquid Functionalization of Cellulose Nanofibers and Their Embedding in HDPE Matrix - Croitoru, Catalin; Patachia, Silvia (International Journal of Polymer Science, 2016)
This paper presents a possible alternative to traditional cellulose nanofibers functionalization, by treatment of the material at low temperatures (25–35°C) with electron-beam irradiated 1-hexyl-3-methylimidazolium chloride ionic liquid. The treatment promotes decreasing the crystallinity of the cellulose with up to 45% and possible imidazolium moieties grafting to cellulose, as demonstrated from FTIR, XRD, and elemental analysis. The grafting determines water vapors uptake values with 50–70% lower and water vapors uptake rate with 50% lower than those of reference cellulose nanofibers. The grafting determined also improved adhesion of the cellulose nanofibers to HDPE, thus contributing to the obtaining of polymer matrix composites with improved properties.
Keywords: cellulose; polyolefins; surface properties